(untitled) (Research, Society and Development, 2022)
With the scenario of the COVID-19 pandemic, caused by the SARS-CoV-2 virus, educational institutions needed to adopt sanitary measures of social distance to maintain education. With this, the academic community needed to adapt to emergency remote teaching, needing to make use of virtual teaching environments. Therefore, the present study aimed to evaluate the influence of academic monitoring in the teaching-learning process of students of the Cell Biology discipline in face of the difficulties brought by remote teaching. Twenty-one answers were obtained from the students, whose results showed: for 76.2% of the interviewees, the methodology applied in the discipline was considered "excellent", and for 19%, "good", leaving the understanding that the way of conducting the teaching was satisfactory to the students. Regarding academic monitoring activities, 100% of the consulted students evaluated positively and reported that the monitors were excellent, above all, for solving doubts, reviewing content and being available when requested. Regarding the profiles of the monitors, 100% of the students highlighted positive aspects, namely: efficient, helpful, proactive, good didactics and important for the learning process. Regarding the difficulties faced in remote teaching, 33.3% of the students indicated the lack of quality internet access and 19.05% indicated the difficulty of concentrating in class. Academic monitoring, in Cell Biology, is an important educational tool, as it helps in the teaching-learning processes, in academic performance and in the adaptation of students to virtual teaching environments, in addition to contributing to the professional and personal training of the monitor and in the teacher/monitor/monitored relationship.